Effects of core-stability training on performance and injuries in competitive athletes - Haugen, T.; Haugvad, L.; Røstad, V. (Sportscience, 2016)
Most competitive athletes perform core-stability training to some extent. In the slideshow accompanying this article we provide a critical overview of scientific studies exploring the relationship between core stability and athletic performance, injury prevention and injury rehabilitation. We also identify methodological limitations and concerns associated with these investigations and provide recommendations for training and rehabilitation. The field suffers from the lack of terminological consensus, and the varying definitions of core can make for confusion as they involve diverse anatomy (e.g., with or without limbs). It is also problematic that parts of the theoretical framework related to core stability have emerged from studies of low back pain, questioning the relevance to athletes. Numerous tests have been proposed to assess core stability, but no universal standards have so far been developed. The proposed core stability tests either have poor validity and reliability or have not been assessed for validity and reliability at all. Targeted core-stability training interventions have in some cases provided positive effects on sport-specific tasks (e.g., throwing velocity). A few cross-sectional studies have reported small-to-moderate relationships among core stability and some sport-specific tasks with strong core components (e.g., baseball pitching/batting, golf, tennis serve). However, a causal relationship between core stability and athletic performance has not been established, owing to limitations in previous study designs. Moreover, poor core stability in isolation is not a predominant risk factor for athletic injuries. Stabilization training of the core may enhance the recovery time for certain injuries, but no better than any other training forms in the long term. In conclusion, isolated core stability training should not be the primary emphasis for programs with the goal of enhancing athletic performance, preventing injuries or reducing injury recovery time. More research in the field is needed for operational definition purposes, developing valid and reliable core stability tests, and exploring cause-effect relationships among core stability and athletic performance, injury prevention and rehabilitation.